To the authors: International Contest of Scholarly Articles results and publication activity brief analysis - D. V. Blinov (Эпилепсия и пароксизмальные состояния)
The material provides a brief overview of authors composition (geography, affiliations) and distribution channels for “Epilepsy and Paroxysmal Conditions” journal content. Information on the number of published studies and relevant temporal citation pattern is provided. The journal is characterized by a wide geography of author groups as well as a steady growth in readership and article citation. The results of the 2024–2025 International Contest of Scholarly Articles are also summarized, the winners in the categories “Original article”, “Review article” as well as the additional nomination “For contribution to the journal development” are named. This information will serve as a valuable landmark for authors-to-be in determining whether the topic and level of their manuscripts are suitable, as well as in choosing options to accelerate editorial process and expand readership: Online First, Fast Track, and full text publication in Russian and English.